Sistem Pakar Diagnosa Penyakit Ibu Hamil Menggunakan Metode Certainty Factor (CF) - Aryu Hanifah Aji; Muhammad Tanzil Furqon; Agus Wahyu Widodo (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2018)
In Indonesia, the death rate of pregnant women was still very high. Lack of knowledge about the perceived symptoms during pregnancy make pregnant women regardless of the specific symptoms that can be harmful and disease records indicate the causes of indirect maternal death in pregnant. Moreover, the risk of pregnant mother mortality is also higher due to the delay in taking the decision factors for referenced. Based on the fact, the proposed solution in the form of expert system diagnosis of diseases of pregnant women using the method of Certainty Factor (CF) that can help recognize diseases during pregnancy to take place based on the perceived symptoms of pregnant women as well as references that should be targeted by the patient. The methods of the CF have a performance system that is capable of running the functional needs and high accuracy percentage results. Moreover the method of CF can describe a level of confidence to the problem at hand. Based on the test results, obtained results 100% functionality of disease diagnosis expert system of pregnant women worked in accordance with a list of system requirements and the system has a level of accuracy of 100%.